(untitled) (Journal of Human Sciences, 2021)
This research is an edition of the interpretation of Al-Waraqat (written by Al-Juwayni (Died 478 AH);. The interpreter is Yusuf ibn Al-Hasan ibn Mahmud Tabrizi (Died 804 AH) The research included an introduction containing: the significance of the study, the reasons for choosing the above-mentioned manuscript, and the research proposal, which was as follows: The first section: The study. It included two chapters: The first chapter: A brief biography about the writer (Al-Juwayni) and the interpreter (Tabrizi). The second chapter: A brief summary about the interpretation. The second section: The manuscript’s edition. It included: a preface describing the copy of the manuscript, the method followed in its edition, the edited text, and then come the references’ index.